非圆齿轮齿条机构及其数学模型 - 黄宗星; 张志瀚; 郑方焱; 刘有源; 陈定方 (Jixie chuandong)
A new non- circular gear rack mechanism is designed according to the principle of gear rack transmission in non- circular gear transmission. The pitch curve of the rack is no longer a straight line,but a plane curve. With the new gear,only a level- 1 transmission can change the speed of the gear to satisfy special motional requirements,as well as the pattern of motion to enhance the dynamics performance of the device. Based on the basic motion relationship and the pitch curve equation of both the gear and rack of the mechanism are deduced. The envelope equations of tooth profile are also acquired based on the meshing principle and the coordinate transformation relationship. Finally,by an example,the geometric design and the ADAMS of contact simulation of the mechanism are accomplished. Through the comparison between the model and the theoretical curve,the feasibility of the device on design and the correctness of the mathematical model is verified.